2012
DOI: 10.1111/j.1600-0706.2012.20153.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of simultaneous interactions of fungal endophytes and arbuscular mycorrhizal fungi with a shared host grass

Abstract: Plants simultaneously associate with multiple microbial symbionts throughout their lifetimes. To address the question of whether the effects of simultaneous symbionts are contingent on the specific identities, we conducted a greenhouse experiment manipulating the presence and identities of arbuscular mycorrhizal fungi (AMF) and fungal endophytes on the shared host grass Elymus hystrix. Each plant host was inoculated with one of two AMF species having varying effects on host growth, or a sterile soil control. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 59 publications
1
44
1
1
Order By: Relevance
“…Dynamic interplays between plant symbionts have been studied widely, such as positive correlations between plant growth‐promoting rhizobacteria and symbiotic fungi colonization . In addition, a few researchers found that competitions existed between endophytic and mycorrhizal fungi in grass–symbiont systems . However, Omacini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic interplays between plant symbionts have been studied widely, such as positive correlations between plant growth‐promoting rhizobacteria and symbiotic fungi colonization . In addition, a few researchers found that competitions existed between endophytic and mycorrhizal fungi in grass–symbiont systems . However, Omacini et al .…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes can alter the functioning of different groups of soil microorganisms, including decomposers (Omacini et al , Jenkins et al ), and other microbial symbionts (Omacini et al , Larimer et al , ). For example, previous studies showed that aerial endophytes and arbuscular mycorrhizal fungi can interact additively (Larimer et al ), antagonistically (Liu et al ) or neutrally regarding host growth (Omacini et al , Mack and Rudgers ), depending on the environmental context and the symbiont and host genotype (Larimer et al , Liu et al ). Even though the coexistence of symbionts in neighbouring plants is highly probable (Stanton , Bonfante and Anca ), studies on their interactive effects are rare.…”
mentioning
confidence: 99%
“…Facultative positive interactions between host species and their associates often involve multiple species (Bronstein 1994, Stanton 2003), including those that differ in spatial and temporal colonization dynamics (Mack and Rudgers 2008, Larimer et al 2012). Variation in the ability of these multiple associate species to provide services to the host is common and can affect the benefits of the relationship (Bronstein 1994, Stachowicz and Whitlatch 2005).…”
mentioning
confidence: 99%